Towards understanding KOH conditioning of amidoxime-based polymer adsorbents for sequestering uranium from seawater. Issue 122 (24th November 2015) - Pan, Horng-Bin; Kuo, Li-Jung; Wood, Jordana; Strivens, Jonathan; Gill, Gary A.; Janke, Christopher J.; Wai, Chien M.
Abstract : Utilizing spectroscopic and microscopic techniques to understand the KOH conditioning process required for preparing high-surface-area amidoxime-based polymer fiber adsorbents for sequestering uranium from real seawater. Abstract : Conditioning of polymer fiber adsorbents grafted with amidoxime and carboxylic acid groups is necessary to make the materials hydrophilic for sequestering uranium from seawater. Spectroscopic techniques were employed to study the effectiveness of the traditional KOH conditioning method (2.5% KOH at 80 °C) on recently developed high-surface-area amidoxime-based polymer fiber adsorbents developed at Oak Ridge National Laboratory. FTIR spectra reveal that the KOH conditioning process removes the proton from the carboxylic acids and also converts the amidoxime groups to carboxylate groups in the adsorbent. With prolonged KOH treatment (>1 h) at 80 °C, physical damage to the adsorbent material occurs which can lead to a significant reduction in the adsorbent's uranium adsorption capability in real seawater during extended exposure times (>21 days). The physical damage to the adsorbent can be minimized by lowering the KOH conditioning temperature. For high-surface-area amidoxime-based adsorbents, 20 min of conditioning in 2.5% KOH at 80 °C or 1 h of conditioning in 2.5% KOH at 60 °C appears sufficient to achieve de-protonation of the carboxylic acid with minimal harmful effects to the adsorbent material. The use of NaOH instead of KOH can also reduce the cost of the base treatment process required for conditioning the amidoxime-based sorbents with minimal loss of adsorption capacity (≤7%).